(untitled) (Scientific journal of the Fergana State University, 2025)
In this article, the composition of Guliob phosphorite located in Sariosia district of Surkhandarya region is studied based on physical and chemical analysis. The total amount of P2O5 in it is from 4.13 to 22.30% and was determined and analyzed in laboratory conditions using photocolorometric, radiometric and ionometric methods. Even if it does not contain P2O5 at the required level, it is possible to modify it with raw materials containing various mineral substances to obtain a new mixed type of fertilizer.